2020
DOI: 10.3389/fimmu.2020.00951
|View full text |Cite
|
Sign up to set email alerts
|

Growth/Differentiation Factor-15 (GDF-15): From Biomarker to Novel Targetable Immune Checkpoint

Abstract: Growth/differentiation factor-15 (GDF-15), also named macrophage inhibitory cytokine-1, is a divergent member of the transforming growth factor β superfamily. While physiological expression is barely detectable in most somatic tissues in humans, GDF-15 is abundant in placenta. Elsewhere, GDF-15 is often induced under stress conditions, seemingly to maintain cell and tissue homeostasis; however, a moderate increase in GDF-15 blood levels is observed with age. Highly elevated GDF-15 levels are mostly linked to p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
282
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 321 publications
(291 citation statements)
references
References 193 publications
(263 reference statements)
5
282
0
4
Order By: Relevance
“…GDF-15 is a member of the anti-inflammatory TGF- β superfamily. While it has been shown to reduce clearance of human rhinovirus and to enhance the risk for virus-induced lung inflammation in mice ( 11 ), it counteracts inflammation ( 8 ), increases the ability of tissues to tolerate inflammatory damage via metabolic adaptation ( 9 ), and reduces tissue infiltration of immune cells ( 8 ). We thus hypothesize that induction of GDF-15 is an adaptation to restore a disturbed balance between pro- and anti-inflammatory cytokines.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…GDF-15 is a member of the anti-inflammatory TGF- β superfamily. While it has been shown to reduce clearance of human rhinovirus and to enhance the risk for virus-induced lung inflammation in mice ( 11 ), it counteracts inflammation ( 8 ), increases the ability of tissues to tolerate inflammatory damage via metabolic adaptation ( 9 ), and reduces tissue infiltration of immune cells ( 8 ). We thus hypothesize that induction of GDF-15 is an adaptation to restore a disturbed balance between pro- and anti-inflammatory cytokines.…”
Section: Discussionmentioning
confidence: 99%
“…Another feature besides viral infectivity and inflammation is the host response and tissue tolerance. An emerging modulator of immune responses ( 8 ) and mediator of inflammation tissue tolerance is the multi-functional anti-inflammatory cytokine growth and differentiation factor 15 (GDF-15) ( 9 ), which physiologically promotes immunotolerance during pregnancy. In mouse models GDF-15 protects the kidney, liver, and other organs from adverse consequences of bacterial and viral sepsis ( 9 , 10 ).…”
Section: Introductionmentioning
confidence: 99%
“…GDF-15 also plays a part in the inflammatory response, and the work by the group of Luan et al showed a GFRAL-related central metabolic adaptation via the regulation of sympathetic outflow and triglyceride metabolism [ 34 ]. Importantly, it has also been emphasized that the manifold actions ascribed to GDF-15 in prior research are limited by contamination of recombinant GDF-15 with TGF β [ 33 , 35 , 36 ]. This indicates that the previous implication of GDF-15 effects on Smad2/3 activity or TGF β RII requires caution and reappraisal [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, it has also been emphasized that the manifold actions ascribed to GDF-15 in prior research are limited by contamination of recombinant GDF-15 with TGF β [ 33 , 35 , 36 ]. This indicates that the previous implication of GDF-15 effects on Smad2/3 activity or TGF β RII requires caution and reappraisal [ 36 ]. On the other hand, it should also be noted that GDF-15 exerts direct effects on immune cells and its immunomodulatory capacity may be independent of centrally regulated mechanisms [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation